The Potential of Artificial Intelligence in Improving Linguistic Competence: A Systematic Literature Review - Rugaiyah, Rugaiyah (Arkus, 2023)
As AI technology develops, we can expect to see more innovative and effective language-learning tools emerge in the future. These tools have the potential to revolutionize the way we learn languages, making them more accessible and enjoyable for learners of all ages and abilities. AI-powered language learning tools can give learners access to a variety of resources, such as dictionaries, grammar guides, and sample texts. It helps learners to broaden their knowledge of the language and to improve their comprehension skills. This study aimed to carry out a systematic review exploring the potential of artificial intelligence in improving linguistic abilities. The literature search process was carried out on various databases (PubMed, Web of Sciences, and Google Scholar) regarding the analysis of artificial intelligence can improve linguistic competence. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The use of AI in improving linguistic competence has great potential. Through personalized and adaptive learning experiences, interactive and immersive learning environments, instant feedback, and access to a wide range of resources, AI can help individuals broaden their language knowledge, improve comprehension, and hone their speaking skills.